Religious Character Foundation In Independent Curriculum: The Strategic Role Of Islamic Religious Education In Schools - Amrullah; Chanda Chansa Thelma (EDUCARE: Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the strategic role of Islamic Religious Education (IRE) in shaping students' religious character through the implementation of the Merdeka Curriculum at the elementary school level. The main focus lies in how religious values are instilled, internalized, and manifested in students’ daily behavior through contextual IRE teaching, religious school programs, and the exemplary conduct of teachers. This research uses a qualitative descriptive approach with case studies. Data were collected through in-depth interviews, direct observations, and document analysis, and were analyzed using data reduction, data display, and conclusion drawing. The findings reveal that students’ religious character development is supported by a synergy between practical IRE learning, daily religious routines, and a school culture that reinforces spiritual values. IRE teachers play a central role in embedding values of faith, morality, and tolerance. The implications highlight the urgency of developing a curriculum that integrates cognitive, affective, and spiritual dimensions, offering a foundation for constructing a contextual and adaptive model of religious character education in the era of the Merdeka Curriculum.